Influence of Audit Tenure, Audit Lag, Opinion Shopping, Liquidity, Leverage, and Profitability on Audit Going Concern Opinion (A Study on Manufacturing Companies Listing in Indonesian Stock Exchange 2015-2019) - Prasetyo, Monita Hanif; Dewi, Veni Soraya; Maharani, Betari (Borobudur Accounting Review, 2021)
Users of financial report need information as a basic for them to making decisions. Going concern audit opinion is a form of audit opinion that is given when there is great doubt about the entity's ability to maintain its survival within a reasonable period of time. This study aims to examine the influence of audit tenure, audit lag, opinion shopping, liquidity, leverage, and profitability of giving a going concern audit opinion. The sample on this study were manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. The reseach using purposive sampling method and processed using logistic regression analysis. The selected sample was 36 companies through predetermined criteria. The results of this study indicate that profitability and opinion shopping has a negative effect, leverage have a positive effect, while audit tenure, audit lag, and liquidity have no effect on going concern audit opinion.